Cross-Jurisdictional Sharing for Emergency Management-Related Public Health: Exploring the Experiences of Tribes and Counties in California - Wimsatt, Maureen A. (Frontiers in Public Health, 2017)
Each American Indian tribe is unique in several ways, including in its relationships with local governments and risk for emergencies. Cross-jurisdictional sharing (CJS) arrangements are encouraged between tribes and counties for emergency management-related population health, but researchers have not yet explored CJS experiences of tribes and counties for emergency management. This investigation used collaboration theory and a CJS spectrum framework to assess the scope and prevalence of tribe-county CJS arrangements for emergency management in California as well as preconditions to CJS. Mixed-methods survey results indicate that tribes and counties have varied CJS arrangements but many are informal or customary. Preconditions to CJS include tribe-county agreement about having CJS, views of the CJS relationship, barriers to CJS, and jurisdictional strengths and weaknesses in developing CJS arrangements. Areas for public health intervention include funding programs that build tribal capacity in emergency management, reduce cross-jurisdictional disagreement, and promote ongoing tribe-county relationships as a precursor to formal CJS arrangements. Study strengths, limitations, and future directions are also discussed.